2016
DOI: 10.1080/10245332.2016.1138621
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and long-term outcomes of warm-type autoimmune hemolytic anemia

Abstract: AIHA has a good prognosis and long-term survival especially in young patients without malignancy. Most patients have responded initially to steroids and have a high response rate to second-line therapy. Carefully adjusted and rapid taper of immunosuppressant is necessary to avoid sepsis complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
27
5
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 21 publications
8
27
5
2
Order By: Relevance
“…These results are similar to the response rates achieved in other centers, where more than 80% of wAIHA cases responded to steroids [81516]. We also found that patients diagnosed with secondary wAIHA responded faster than those with primary wAIHA (18 vs. 37 days, P =0.05).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These results are similar to the response rates achieved in other centers, where more than 80% of wAIHA cases responded to steroids [81516]. We also found that patients diagnosed with secondary wAIHA responded faster than those with primary wAIHA (18 vs. 37 days, P =0.05).…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, probably due to the underlying autoimmune disorders, secondary wAIHA patients relapsed more frequently than primary wAIHA patients that the primary wAIHA patients had a median DFS of 51 weeks versus 28 weeks in patients with secondary wAIHA ( P =0.018). It is important to state that other studies have found no statistically significant differences in terms of DFS between primary and secondary wAIHA [1621]. Among the causes of secondary wAIHA, we only found a statistically significant difference in TB levels at diagnosis in the patients with autoimmune-related wAIHA.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Relapse occurred in approximately 50% of patients with primary AIHA, but the relapse rate for AIHA posttransplants had rarely been reported. 26,27 In our study, the relapse rate was higher in the Whether AIHA contributes to increase TRM has not yet been defined. 7,12,18 Daikeler et al suggested that AIHA was not attributable to TRM.…”
Section: Discussionmentioning
confidence: 60%